Improving input from research to environmental policy: challenges of structure and culture - Clark, R; Holmes, J (2010)
In making better use of research to inform environmental policy, advisers and policy people in UK government departments and agencies face a number of challenges, as do researchers and experts. Interviews and a workshop revealed that the challenges in obtaining information from environmental research to inform policy mostly arise from the different social structures and cultures of the researchers and advisers/policy people. They also identified potential solutions that enable social interaction and that increase shared understanding of the different cultures. Examples include more opportunities for advisers, policy people, researchers and experts to meet and maintain contact and improved availability and accessibility of policy-relevant research findings. © Beech Tree Publishing 2010.